The Effects of a Cultivar and Silicon Treatments on Grain Parameters and Bioactive Compound Content in Organic Spring Wheat - Iwona Kowalska; Mariusz Kowalczyk; Jarosław Mołdoch; Sylwia Pawelec; Paweł Radzikowski; Beata Feledyn-Szewczyk (Foods, 2025)
To address the need for improved nutritional value of organically grown wheat, this study investigated the impact of silicon treatments (AdeSil, ZumSil) on yield, health status, and bioactive compound content in spring wheat cultivars. The 2019–2020 research evaluated different application variants: seed dressing, foliar sprays, and their combinations. Comprehensive seed dressing combined with two foliar treatments, (variant B) and two foliar treatments (variant C), significantly increased yield (by an average of 8.9% and 7.6% vs. control, respectively). These variants beneficially affected fungal disease resistance mainly in the stressful 2019; in optimal 2020, they showed no clear advantage over the control, which performed similarly or better. Seed dressing (variant D) increased total phenolic acids (PAs) content and antioxidant activity, with the spelt cv. Wirtas exhibiting the highest levels. Silicon treatments modified alkylresorcinols (ARs) content, but effects depended on the year, cultivar, and application variant, not always exceeding the control. Silicon treatments, especially when applied in combination (seed dressing and foliar application), can improve spring wheat yield and favorably modify PAs content, enhancing grain nutritional value. However, the plant response regarding health status and ARs content is strongly conditioned by cultivar specificity and the prevailing environmental conditions of the growing year.